2006
DOI: 10.1289/ehp.8271
|View full text |Cite
|
Sign up to set email alerts
|

Workgroup Report: Indoor Chemistry and Health

Abstract: Chemicals present in indoor air can react with one another, either in the gas phase or on surfaces, altering the concentrations of both reactants and products. Such chemistry is often the major source of free radicals and other short-lived reactive species in indoor environments. To what extent do the products of indoor chemistry affect human health? To address this question, the National Institute for Occupational Safety and Health sponsored a workshop titled “Indoor Chemistry and Health” on 12–15 July 2004 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 40 publications
(47 reference statements)
3
56
1
Order By: Relevance
“…The median levels of formaldehyde and benzaldehyde were higher outdoors than indoors, indicating mainly outdoor sources. It is well known that ozone and NO 2 have an important role in reactive indoor and outdoor chemistry where different aldehydes are formed (Weschler, 2001;Weschler et al, 2006). Such reactive chemistry is often the major source of free radicals and other short-lived reactive compounds in indoor environments (Weschler et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The median levels of formaldehyde and benzaldehyde were higher outdoors than indoors, indicating mainly outdoor sources. It is well known that ozone and NO 2 have an important role in reactive indoor and outdoor chemistry where different aldehydes are formed (Weschler, 2001;Weschler et al, 2006). Such reactive chemistry is often the major source of free radicals and other short-lived reactive compounds in indoor environments (Weschler et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that ozone and NO 2 have an important role in reactive indoor and outdoor chemistry where different aldehydes are formed (Weschler, 2001;Weschler et al, 2006). Such reactive chemistry is often the major source of free radicals and other short-lived reactive compounds in indoor environments (Weschler et al, 2006). The health significance of reactive indoor chemistry has been documented for terpene oxidation products (Rohr, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the NO3 concentration remained low during the whole simulation, never exceeding 0.1 ppt. Although it has been suggested that NO3 concentrations could be as high as 1 ppt indoors, 40 other modelling studies have also predicted low concentrations. 24 Clearly, measurements of NO3…”
Section: Production Of Secondary Species: Impact On Indoor Air Qualitymentioning
confidence: 99%
“…Indoor volatile organic compounds (VOCs) may be associated with signs and symptoms of ill health [1][2][3][4][5][6][7][8]. Though the associations of VOCs to ill health have been controversially discussed [9,10] some data show that even small dosages may already account for these observed health effects [2,4,8].…”
Section: Introductionmentioning
confidence: 99%